Molecular epidemiology of echovirus 30: temporal circulation and prevalence of single lineages - Palacios, Gustavo (2002)
Fil: Palacios, Gustavo. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Neurovirosis; Argentina.